Prekmurska gorička lončarska terminologija - Koletnik, Mihaela (Slavistična revija, 2007)
The study of the pottery terminology in the Prekmurje Goričko subdialect compiled numerous pottery technical terms that are presently alive in Pečarovci in Goričko. The majority of the terms are one-word and Slavic by origin. Most terms borrowed from other languages are Germanic and Romance, introduced into the Prekmurje dialect through German.
Keywords: besedje; besedoslovje; contact languages; dialectology; lončarsko besedje; lončarstvo; pottery; Prekmurje dialects; prekmursko narečje; Slovene dialects; Slovene language; slovenska narečja; slovenščina; strokovno izrazje; terminology; vocabulary